Interface detection by picosecond Laser-Induced Breakdown Spectroscopy (LIBS): Application to a physical vapor deposited tungsten layer on a copper-chromium-zirconium substrate. (June 2022) - Favre, Aurélien; Morel, Vincent; Bultel, Arnaud; Godard, Gilles; Idlahcen, Said; Diez, Mathilde; Grisolia, Christian; Perry, Frédéric
Highlights: Ablation experiments performed with Gaussian laser pulses in picosecond regime. Ablation rate measured on tungsten (bulk and physical vapor deposited on CuCrZr) and directly on CuCrZr. Observation of micro-craters corresponding to higher ablation rates. Interface precisely located using LIBS spectroscopy. Thickness determined in satisfactory agreement with other techniques. Abstract: The Laser-Induced Breakdown Spectroscopy (LIBS) technique is tested to control the ablation of a tungsten layer having a dozen micrometers thickness obtained by physical vapor deposition (PVD) on a CuCrZr substrate figuring plasma facing components used in the WEST tokamak. In the conditions of a Gaussian laser source with a wavelength of 532 nm, 30 ps as laser time duration and irradiance of ∼ 10 17 W m −2 in air at atmospheric pressure, the mean ablation rate of the PVD tungsten is 90 nm per pulse, which is much lower than the one of bulk tungsten measured at 500 nm per pulse. The ablation process can lead to the formation of secondary craters not directly driven by the laser irradiance distribution. The ablation rate on CuCrZr is measured at 600 nm per pulse. Measuring the deposited layer thickness requires to spectroscopically monitor the CuCrZr components to avoid any damage of the substrate. We show that this can be performed in real time. A more secure process based on the use of a defocused laser beam is tested and leads to significantly lower ablation rate with the same precision for the thickness measurement. The increase in the ablation radius may be used to clean substrates polluted by tungsten layers.